Psychology between Psychological and Real Reality – Which One is Explored by Psychology? - Todorović, Milorad V; Jović, Vladimir M. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
There is still no a precise answer what is generally considered a reality in psychology, and what kind of reality is a object of work in psychological praxis. This is primarily related to the lack of clarity regarding the relationship between subjectivity and psychic reality. The introduction of psychic reality as the decisive factor in the emergence of pathology and relativization of real reality enabled psychoanalysis to shift the focus from the real, external, objective, physical to the unconscious fantasies, by which the inner world got its rightful place in the construction of ’mental’. Although psychological reality is located in the unconscious as well, Freud did not intend to declare the whole experience for purely subjective, but he thought that experience reflects unconscious influences, more precisely, unconscious desires and fantasies. Since all forms of knowledge are subjective, therefore, subject to the influence of the unconscious, it seems that psychic reality and subjectivity reflect unconscious influences to varying degrees, i.e. they show varying degrees of objectivity. This is corroborated by conscious states such as guilt and anxiety, which are such only because they are the result of unconscious dynamics triggered by the transfer, switched to an objective situation. It is not debatable that the sensory data as perceptual knowledge of external objects have a greater degree of objectivity than pure fantasy which are largely subjective and are very little based on the objective. Stressing the importance of the psychological reality both for the structure and for the psychology that seeks to understand the same structure, here it will be stressed the ubiquity of that reality based on the ability of an infant to form primitive object relations in reality and in fantasy from the very beginning of life.Already at the very beginning of life the child finds himself in a vicious circle where the real experiences inevitably influence the unconscious fantasy, and then the fantasy affects the reality. So constructed psychic reality remains to exist during a lifetime in each subject. It is completely the same to say that the weight of the pathology determines the importance of the role of psychological reality or that any strengthening of psychic reality is reflected in the production of the pathological.